Effect of Empagliflozin On Liver Enzymes of Patients In Non-Alcoholic Steatohepatitis In Type 2 Diabetes Mellitus - Wazir, Nauman; Ur Rehman, Shafqat; Arshad, Muhammad; Wazir, Muhammad Zubair; Khan, Shehriyar; Ullah, Muhammad Saqib (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To assess the effect of 10 mg and 25 mg once daily Empagliflozin on liver enzymes of patients of non-alcoholic steatohepatitis in patients of type 2 diabetes mellitus (T2DM). METHODOLOGY The study design was Quasi Experimental. Thirty three adult patients of Type 2 diabetes mellitus (T2DM) who were already on 2000 mg of Metformin and 100 mg of Sitagliptin and were having suboptimal glycemic control (HBA1C > 7% <12%), had elevated Alanine Transaminase (ALT) levels and had ultrasonographic features consistent with non-alcoholic fatty liver disease (NAFLD) were divided into three groups, one group receiving 10 mg Empagliglozin as add-on treatment (Group A), the second group receiving 25 mg of Empagliflozin (Group B) as an additional treatment, and the third group continued with previous medications without any additional treatment (Group C). HbA1C levels and ALT levels of all the three groups were taken at baseline and at 12 weeks. RESULTS Total patients and their mean ages in group A, B and C were 10, 12 and 11 and 52.40 ±4.24 years, 52.42 ± 5.27 years and 52.34 ± 4.37 years, respectively. There was a statistically significant (p > 0.05) decrease mean ALT levels in Group A pre-treatment and 12 weeks post-treatment. Similarly, there was a statistically significant (p > 0.05) decrease mean ALT levels in Group B pre-treatment and 12 weeks post-treatment. CONCLUSION Empagliflozin in both 10mg and 25 mg once daily doses cause statistically significant reduction in ALT levels in patients with NASH associated with T2DM